Metabolic pathway rewiring in engineered cyanobacteria for solar-to-chemical and solar-to-fuel production from CO2. Issue 1 (1st January 2018) - Woo, Han Min
ABSTRACT: Photoautotrophic cyanobacteria have been developed to convert CO2 to valuable chemicals and fuels as solar-to-chemical (S2C) and solar-to-fuel (S2F) platforms. Here, I describe the rewiring of the metabolic pathways in cyanobacteria to better understand the endogenous carbon flux and to enhance the yield of heterologous products. The plasticity of the cyanobacterial metabolism has been proposed to be advantageous for the development of S2C and S2F processes. The rewiring of the sugar catabolism and of the phosphoketolase pathway in the central cyanobacterial metabolism allowed for an enhancement in the level of target products by redirecting the carbon fluxes. Thus, metabolic pathway rewiring can promote the development of more efficient cyanobacterial cell factories for the generation of feasible S2C and S2F platforms.